Attic conversions as an environmental and profitable urban strategy from empty attics to sustainable homes - Engelbrektsson, Lina; Karlsson Inde, Selma (My University, 2025)
As cities grow and sustainability demands increase, the construction sector faces the challenge of meeting housing needs while minimizing environmental impact. This thesis explores attic conversions as a strategic form of adaptive reuse, offering a dual potential: reducing carbon emissions and generating economic value. The study compares attic conversions to new construction, based on semi-structured interviews with industry professionals, a national resident survey and a literature review. Findings show that attic conversions can lower carbon emissions by up to 71% compared to new builds, primarily due to the reuse of existing structural elements. However, the profitability of these projects is heavily influenced by factors such as location, ownership models, volume and the experience of each project team. Furthermore, the study identifies regulatory gaps and inconsistent measurement standards as barriers to broader adoption of attic conversions, despite their strong alignment with national sustainability goals. The thesis concludes that attic conversions should be recognized not only as a technical solution but as a powerful urban development strategy – one that requires coordinated public policy, targeted support and cross-disciplinary collaboration to unlock its full potential in the Swedish housing context. Additionally, attic conversions represent a unique market niche due to their rare combination of modern functionality and historic architectural charm.
Keywords: Adaptive Reuse, Attic Conversions, New Construction, Project Management, Urban Housing, Sustainability, CO₂ Emissions, Life Cycle Assessment, Profitability, Renovation vs New Construction